Sri Lanka foreign affairs : a review of activities carried out during the period 1994-1998 with highlights of Sri Lanka's foreign relations in the post-independence period. - Sri Lanka. Vidēśa Kaṭayutu Bhāra Amātyāṃśaya (Colombo : Ministry of Foreign Affairs, Sri Lanka, 1998)
Brought out to commemorate the 50th anniversary of Sri Lanka's independence.
Keywords: Sri Lanka